2014
DOI: 10.1371/journal.pone.0086759
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Circulating Tumor Cells in Freely Moving Awake Small Animals Using a Miniaturized Intravital Microscope

Abstract: Metastasis, the cause for 90% of cancer mortality, is a complex and poorly understood process involving the invasion of circulating tumor cells (CTCs) into blood vessels. These cells have potential prognostic value as biomarkers for early metastatic risk. But their rarity and the lack of specificity and sensitivity in measuring them render their interrogation by current techniques very challenging. How and when these cells are circulating in the blood, on their way to potentially give rise to metastasis, is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…This has been confirmed by Juratli et al who observed high variations in CTC numbers in consecutive IVFC 5-min imaging windows and in sequentially drawn patient blood samples [45]. We envision that this problem may be addressed in the future using continuous intravital imaging methods in freely moving small animals [34].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This has been confirmed by Juratli et al who observed high variations in CTC numbers in consecutive IVFC 5-min imaging windows and in sequentially drawn patient blood samples [45]. We envision that this problem may be addressed in the future using continuous intravital imaging methods in freely moving small animals [34].…”
Section: Discussionsupporting
confidence: 59%
“…Using two rounds of fluorescence activated cell sorting (FACS), we established a stable cell line (denoted 4T1-GL) that expresses high levels of the bifusion reporter gene for at least 12 passages in culture [34]. Using an additional round of FACS, we selected the 4T1-GL-TS population as the 5% brightest cells among 4T1-GL cells, based on GFP fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…S9), suggesting the potential for reinitiation of cluster transit after occlusion and/or a slow "creeping" transit behavior. This observation may explain the reportedly short circulating half-lives of CTCs (37) and CTC clusters (9) because increased residence times within capillaries may inhibit/delay their detection or sampling from larger vessels. Further studies are needed to explore these phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…For all bioluminescence work, we used genetically-modified GBM2, GBM39 and U87-MG whereby cells were transfected with lentiviral vectors that expressed either firefly luciferase (for GBM39) or a fusion protein of GFP and firefly luciferase (for GBM2 and U87) [22, 23]. All BLI work done on an IVIS Spectrum (Xenogen Corporation, Alameda, CA).…”
Section: Methodsmentioning
confidence: 99%